Quimioterapia neoadjuvante torna ressecável carcinoma de cabeça de pâncreas - Marco Antônio Cezário de Melo (Revista do Colégio Brasileiro de Cirurgiões)
We present a case of non-resectable head pancreatic cancer by mesenteric venous invasion in which treatment with Gemcitabine (Gemzar) 1.000 mg/m 2 weekly for 3 weeks, followed by a 1-week rest, normalized CA 19.9 and promoted tumor resecability in a second operation (ultrasound, helicoidal tomography and magnetic ressonance exams). The value of the adjuvant treatment (radiochemotherapy) and the association with immunotherapy (Interferon) is discussed.